Analysis of Increase in Non-Taxable Income (NTI) in relation with Implementation of Equality Principles and Taxation Base Principles - Jonrisman Sinaga; Machfud Sidik (Ilomata International Journal of Tax and Accounting, 2019)
This research discussed an increase of non-taxable income that expected to be able to step-up the purchasing power, especially in consumption. Increase on non-taxable income which applies has not reflected the equality principle in taxation like what people feel, where non-taxable income has not touched the sense of equality. It becomes a dilemma to the government for expanding the taxation base by increasing non-taxation income. Increase in non-taxable income can reduce the taxation base. Practice in Simplicity or Easy of Tax Administration concept make the application on equality principle in taxation is not maximal, because non-taxation income equalizes all taxpayers’ —rich nor poor, sick nor health, and citizens who are on education. Implementation of this concept is inseparable from taxpayer database condition which based on Identity Number that has not beneficial. Increase of non-taxable income also decreases the Tax Revenue Article 21 where the revenue decreased by 4.65% in 2016. Increase in non-taxable income is expected to boost the purchasing power of citizen, hence demand on goods and service will increase. With the increase of demand, production to absorb the employment that becomes the object of Non-Taxable Income Article 21.